Observations of the uptake of carbonyl sulfide (COS) by trees under elevated atmospheric carbon dioxide concentrations (Biogeosciences, 2012)
. Global change forces ecosystems to adapt to elevated atmospheric concentrations of carbon dioxide (CO2). We understand that carbonyl sulﬁde (COS), a trace gas which is involved in building up the stratospheric sulfate aerosol layer, is taken up by vegetation with the same triad of the enzymes which are metabolizing CO2, i.e. ribulose-1,5- bisphosphate carboxylase/oxygenase (Rubisco), phosphoenolpyruvate carboxylase (PEP-Co) and carbonic anhydrase (CA). Therefore, we discuss a physiological/biochemical acclimation of these enzymes affecting the sink strength of vegetation for COS. We investigated the acclimation of two European tree species, Fagus sylvatica and Quercus ilex, grown inside chambers under elevated CO2, and determined the exchange characteristics and the content of CA after a 1–2 yr period of acclimation from 350 ppm to 800 ppm CO2. We demonstrate that a compensation point, by deﬁnition, does not exist. Instead, we propose to discuss a point of uptake afﬁnity (PUA). The results indicate that such a PUA, the CA activity and the deposition velocities may change and may cause a decrease of the COS uptake by plant ecosystems, at least as long as the enzyme acclimation to CO2 is not surpassed by an increase of atmospheric COS. As a consequence, the atmospheric COS level may rise causing an increase of the radiative forcing in the troposphere. However, this increase is counterbalanced by the stronger input of this trace gas into the stratosphere causing a stronger energy re- ﬂection by the stratospheric sulfur aerosol into space (Bruhl ¨ et al., 2012). These data are very preliminary but may trigger a discussion on COS uptake acclimation to foster measurements with modern analytical instruments.

Exchange of short-chain oxygenated volatile organic compounds (VOCs) between plants and the atmosphere: A compilation of field and laboratory studies (Journal of Atmospheric Chemistry, 2001)
Field and laboratory investigations of the exchange of the short-chain organic acids – formic acid and acetic acid – as well as their homologous aldehydes are discussed. Both acids are substantially released from several plant species. Emission measurements under ﬁeld conditions are compiled to give an overview of three years of measurements. Emission rates from several tree species were found in the range between zero and 60 nmoles m−2 min−1 for acetic acid and between zero and 90 nmoles m−2 min−1 for formic acid though also a deposition has been observed to orange trees. Investigations under laboratory conditions showed an order of magnitude lower emission rates with signiﬁcant differences under light and dark conditions, and a deposition was observed under certain conditions. Hence, low emission rates or even a bi-directional exchange, emission as well as deposition have to be taken into account. Further differences between ﬁeld and laboratory studies are discussed considering age of trees, stress effects and a potential production of acids by photochemical conversion of precursors inside enclosures during sampling. Field data on the exchange of formand acetaldehyde show a complex behavior. We found emission as well as uptake. The bi-directional exchange is signiﬁcantly triggered by the ambient mixing ratios of both aldehyde species and exhibits a compensation point. Further studies are needed for generalization of the exchange of these and potentially also for other compounds

Biogenic volatile organic compounds (VOC): An overview on emission, physiology and ecology (JOURNAL OF ATMOSPHERIC CHEMISTRY, 1999)
This overview compiles the actual knowledge of the biogenic emissions of some volatile organic compounds (VOCs), i.e., isoprene, terpenes, alkanes, alkenes, alcohols, esters, carbonyls, and acids. We discuss VOC biosynthesis, emission inventories, relations between emission and plant physiology as well as temperature and radiation, and ecophysiological functions. For isoprene and monoterpenes, an extended summary of standard emission factors, with data related to the plant genus and species, is included. The data compilation shows that we have quite a substantial knowledge of the emission of isoprene and monoterpenes, including emission rates, emission regulation, and biosynthesis. The situation is worse in the case of numerous other compounds (other VOCs or OVOCs) being emitted by the biosphere. This is reflected in the insufficient knowledge of emission rates and biological functions. Except for the terpenoids, only a limited number of studies of OVOCs are available; data are summarized for alkanes, alkenes, carbonyls, alcohols, acids, and esters. In addition to closing these gaps of knowledge, one of the major objectives for future VOC research is improving our knowledge of the fate of organic carbon in the atmosphere, ending up in oxidation products and/or as aerosol particles.

Exchange of atmospheric formic and acetic acids with trees and crop plants under controlled chamber and purified air conditions (Atmospheric Environment, 1998)
We investigated the exchange of formic and acetic acids between the atmosphere and various tree species such as beech (Fagus sylvatica L.), ash (Fraxinus excelsior L.), spruce (Picea abies L.) Karst, holm oak (Quercus ilex L.), and birch (Betula pendula L.). and some crop-plant species such as corn (Zea mays, var. Banjo), pea (Pisum sativum, var. Solara), barley (Hordeum vulgare, var. Igri) and oat (Avena sativa, var. Wiesel). All experiments were done with dynamic enclosures ßushed with puriÞed oxidant-free air, containing only low or controlled amounts of the two acids. SigniÞcant and light-triggered emission of both acids from all tree species was observed. For one tree species (ash) a seasonal large increase in fall due to early leaf decomposition was found. The standard emission factors (30¡C and PAR"1000 kmol m2 s~1) given as (nmol m~2 min~1) for acetic and formic acids, respectively, were 8.1 and 29.7 (ash, autumn), 1.0 and 3.3 (ash, summer), 0.9 and 1.4 (beech), 0.7 and 1.45 (spruce), 1.9 and 2.4 (Holm oak) and 1.7 and 6.7 (birch). Rough estimation of global annual emissions range between 20 and 130 Gmol formic acid and 10 and 33 Gmol acetic acid. These numbers reßect a 15Ð30% contribution by forest emissions to the continental organic acid budget. As compared to the global total NMHC emissions low molecular weight organic acids are of minor importance. In contrast to the trees, none of the crop-plant species investigated showed an emission, but always a clear deposition of both acids. Both emission from trees as well as uptake by the agricultural plants could be related to transpiration rates and leaf conductances

Simultaneous field measurements of terpene and isoprene emissions from two dominant Mediterranean oak species in relation to a north American species (Atmospheric Environment, 1998)
ÐWe investigated the emission of monoterpenes and isoprene from tree species growing at a site near Montpellier (South France). We compared the emission pattern and behaviour of two important oak species representative of the Mediterranean ecosystem, namely, Quercus ilex (Holm oak), a strong monoter- pene emitter, and Quercus pubescens (White oak), a strong isoprene emitter by measuring the two species growing side by side simultaneously. Additionally, we included a Californian oak species Quercus agrifolia (Coast Live Oak), which is anatomically and morphologically comparable with Quercus ilex. The data show that Live Oak and Holm oak though they appear identical, di¤er as far as the emission of terpenoids is concerned, emitting isoprene or terpenes, respectively. The isoprene emitting White oak and the monoter- pene emitting Holm oak react identically to the same environmental conditions, ßuctuating light and temperature, indicating that close metabolic pathways are involved in the actual emission of the C5 and C10 compounds from these two species, as seen under Þeld conditions. ( 1998 Elsevier Science Ltd. All rights reserved

EMISSION OF SHORT CHAINED ORGANIC ACIDS , ALDEHYDES AND MONOTERPENES FROM QUERCUS ILEX L . AND PINUS PINEA L . IN RELATION TO PHYSIOLOGICAL ACTIVITIES , CARBON BUDGET AND EMISSION ALGORITHMS (Atmospheric Environment, 1997)
We report on the emission of monoterpenes, short-chained organic acids and aldehydes from Mediterranean oak (Quercus ilex L.) and pine (Pinus pinea L.). All studies were done with dynamic cuvettes enclosing intact branches at the top of the canopy flushed with ambient air. Daily trends are compared with the photosynthetic active radiation (PAR), leaf temperature and the physiological activities of the enclosed branches, i.e. assimilation and transpiration, with special attention on the carbon budget. Oak emits monoterpenes in high amounts, up to 2% of the assimilated carbon. As compared with monoterpenes, short-chained organic acids and aldehydes are of minor importance for oak. However, on a leaf dry-weight basis equal amounts of acids and aldehydes are released from oak and pine. As pine emitted only low amounts of terpenes (below 0.2% of the assimilated carbon) the release of terpenes and oxygenated compounds is of equal importance for this species. A comparison of a modelled light and temperature driven emission with the observed volatile organic compounds (VOC) emissions showed good agreement for monoterpenes as well as for organic acids emitted in the case of oak. For pine only the release of acids showed an adequate relation to the algorithm data, whereas the terpene emissions seemed to be dominated by temperature effects

An overview of the Castelporziano experiments (Atmospheric Environment, 1997)
This paper reviews the major outcomes of the measuring campaigns performed at the Castelporziano nature preserve near Rome, Italy, by 14 European laboratories as part of the BEMA (Biogenic Emissions in the Mediterranean Area)-project. Six campaigns of 1–4 weeks duration were carried out in different seasons of the years 1993–1994 at semi-continuously running test plots in the nature reserve, representing common Mediterranean vegetation types. The aim was to characterise, at the different test plots, the atmospheric chemical and meteorological situations, the plant biomass and physiology, the type, amount and controls of emissions from different plants by means of branch enclosures, and the BVOC emission fluxes from different ecosystems, by scaling up enclosure data from individual sources, and by measuring fluxes directly by use of micrometeorological methods. An important focus during the initial phase of the five year BEMA-project was the harmonisation and improvement of the analytical, physiological and micrometeorological methods used, and the development and testing of new methods for measuring BVOC fluxes.

EMISSION OF MONOTERPENES AND ISOPRENE FROM A MEDITERRANEAN OAK SPECIES QUERCUS ILEX L. MEASURED WITHIN THE BEMA (BIOGENIC EMISSIONS IN THE MEDITERRANEAN AREA) PROJECT EMISSIONS IN THE M E D I T E (Atmospheric Environment, 1996)
We report on some results of our studies of monoterpene and isoprene emissions and the physiological activities of an oak species (Quercus ilex L.) under the Mediterranean climatic conditions found at Castel Porziano (Rome) in June 1993. The oak species Quercus ilex L. was found to emit mainly monoterpenes in high amounts. Isoprene emissions were negligible. Diel cycles of monoterpene emissions showed correlation with light and the diel behaviour of photosynthetic CO2 assimilation, transpiration and stomatal corductance. Temperature dependence seemed to be of minor importance.